Three-Dimensional Relationships Among Traffic Flow Theory Variables: A Comparative Study - Richardson, William Robert Charles (My University, 1990)
This paper is a further investigation of Gilchrist and Hall's work on the three-dimensional relationships in traffic flow theory variables (Gilchrist and Hall, 1989). The investigation examines the three variables of traffic flow (speed, volume, and occupancy). Gilchrist and Hall's data is then compared with data used in this analysis. The traffic variables are first examined by the traditional two-dimensional model and then they are examined obliquely in three-dimensional space. The resulting oblique views of the data are reviewed for points of agreement with conclusions made by Gilchrist and Hall. Resultant views of the data suggest that there is a plane along which all of the uncongested data fall. However, this phenomena only occurs when there is a wide range of speed values in the data set. The results also suggest that low-speed congested data do not lie on the same plane as do the uncongested data. It is concluded that low-speed congested data do not lie on a plane at all.
Keywords: three-dimensional, relationships, traffic flow, variables, comparative, speed, volume, occupancy